Early College, Continued Success: Longer-Term Impact of Early College High Schools. Issue 1 (2nd January 2021) - Song, Mengli; Zeiser, Kristina; Atchison, Drew; Brodziak de los Reyes, Iliana
Abstract: Following up on a previous impact study of Early Colleges (EC) based on retrospective admission lotteries, this study assessed longer-term impacts on students' postsecondary outcomes with 4 more years of data. The study found that students who won EC admission lotteries were significantly more likely to enroll in college, enroll in 2-year colleges, complete a college degree, complete associate's degrees or certificates, and complete bachelor's degrees within 6 years after expected high school graduation than control students. Moreover, it found that treatment students completed postsecondary degrees earlier and faster than control students. Consistent with EC's focus on college exposure during high school, the EC impacts on college enrollment and the completion of associate's degrees largely occurred within high school. The study also found that EC impacts did not vary significantly by students' demographic characteristics; however, some impacts were significantly stronger for students with higher levels of prior achievement.